Effects of Banditry and Illegal Logging on Conservation in Kainji Lake National Park, Nigeria - S. M. Ayeni; P. N. Meduna; A. A. Babatunde (Journal of Applied Sciences and Environmental Management)
The objective of tis paper is to investigate the Effects of Banditry and Illegal Logging on Conservation in Kainji Lake National Park, North Central, Nigeria using standard procedures by distributing one hundred and ninety four (194) questionnaires, of which one hundred and thirteen (113) were completed and returned. The result of demographic characteristics of respondents indicates that the male respondents were dominant (75.7%). Furthermore, 51.4% of the sampled populations’ falls between age group 35-44 years, followed by 25-34 years with 30.8% and age group 45 and above were the least (17.8%). The finding further revealed that majority of the respondents was married (71.0%) and 59.8% of the respondents had tertiary education while 40.2% had secondary education. Also, majority of the respondents are Muslims (71.0%) while 29.0 are Christian. Majority of the respondents (52.3%) had worked between 11-20 years. The respondent’s monthly income of the majority (55.1%) respondents is between N50, 000-99,000. The species of tree and animals that are mostly affected by illegal logging includes; Adansoniadigitata, Afzelia africana, Milicia excels etc. The animal species includes Grim duiker, Guinea fowl, Bushbuck, Rabbit etc. The effects of banditry and illegal logging on wildlife conservation in Kainji Lake are destruction of habitat (45.1%) and decline in wildlife population (38.1%) recorded the highest percentages, followed by loss of biodiversity (11.5%) while climate change is the least with 4.4%. The management strategies to proffer solution to the menace in the study area in which adequate field equipment for staff recorded the highest with 31.9%, followed by adequate staff training with 30.1% while demarcation of Park boundary recorded the least with 15.0%. The study concludes that there are banditry and illegal logging activities in Kainji Lake National Park.